Can Autistic Traits Severity Predict Autism Parenting Stress? - Ibrahim, Rabab Khalil; Al-Juboori, Ali Kareem (Journal of Contemporary Medical Sciences, 2023)
Objectives: To investigates the mediating role of autistic traits severity in parenting stress among parents of children with autism spectrum disorder. Methods: A descriptive correlational design was used in this study which includes a simple random sample of parents of children with autism who age 2-12-years referred to the Alsubtain Academy autism center during 2022 in Karbala provinance, Iraq. Results: Most parents are stressed experience 52 % of total sample and most children have severe autistic traits. Furthermore, autistic traits severity positively predicted parental autism stress. Conclusion: Parents of children with severe traits of ASD tend to have high level of parenting stress, Other variables such as age of child on diagnosis, child age, parental gender and family type have no significant effect on parenting stress.